2020
DOI: 10.1159/000508027
|View full text |Cite
|
Sign up to set email alerts
|

Intramural Hematoma Shape and Acute Cerebral Infarction in Intracranial Artery Dissection: A High-Resolution Magnetic Resonance Imaging Study

Abstract: Background: Intracranial artery dissection (IAD) is gaining recognition as an important cause of stroke, but limited information is available about the morphology of the dissection. This study aimed to investigate the relationship between acute cerebral infarctions and the shape of hematoma in patients with IADs using high-resolution magnetic resonance imaging (HRMRI). Methods: We enrolled consecutive patients who presented with vascular headaches, transient ischemic attacks, or ischemic strokes with acute IAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…To support our hypothesis, we performed a sub-analysis including patients with or without intramural hematoma (IMH, a pathognomonic marker of SCCAD) (10)(11)(12). Interestingly, 85 (39.5%) cases with SCCAD had IMH; among them, 15 (17.6%) patients had at least one autoimmune disease; 130 (60.5%) cases of SCCAD had no IMH, and 12 (9.2%) patients had at least one autoimmune disease.…”
Section: Autoimmune Disease and The Risk Of Sccadmentioning
confidence: 92%
“…To support our hypothesis, we performed a sub-analysis including patients with or without intramural hematoma (IMH, a pathognomonic marker of SCCAD) (10)(11)(12). Interestingly, 85 (39.5%) cases with SCCAD had IMH; among them, 15 (17.6%) patients had at least one autoimmune disease; 130 (60.5%) cases of SCCAD had no IMH, and 12 (9.2%) patients had at least one autoimmune disease.…”
Section: Autoimmune Disease and The Risk Of Sccadmentioning
confidence: 92%
“…Lee's study showed the shape of intramural hematomas was independently associated with cerebral infarction. Proximal dominant intramural hematomas may be more closely associated with the cerebral infarctions than the distal dominant intramural hematomas ( 9 ). In addition, pseudoaneurysms are less common and occur because of partial transection of the artery.…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysmal protrusion, including dissecting aneurysm and pseudoaneurysms, was de ned as an aneurysm with a vessel diameter exceeding the diameter of the normal distal artery by ≥ 1.5-fold [12] (Figure 1, green arrows in Figure 5, and Figure 6). IMH was de ned as a false lumen lled with hematoma without blood ow, showing iso-or hypersignal shadow on images before angiography [13,14] (red arrows in Figure 3). The degree of wall enhancement of the blood vessels was divided into 3 levels as follows: Level 0, similar to a normal blood vessel wall; Level 1, greater than Level 0 but less than venous wall enhancement; Level 2, similar to or greater than venous wall enhancement.…”
Section: Image Analysismentioning
confidence: 99%